Consumption of takeaway and fast food in a deprived inner London Borough: are they associated with childhood obesity?. Issue 3 (20th June 2012) - Patterson, Rachel; Risby, Alexander; Chan, Mei-Yen
Abstract : Objective: A major concern is the ubiquitous presence of fast food and takeaway outlets within easy walking distance of schools, particularly in the light of the increasing burden of childhood obesity. Here, the associations between the schoolchildren's weights, their consumption of fast food and takeaway outlets were examined in a deprived inner London Borough. Design: This is a cross-sectional study. Participants: 193 schoolchildren (aged between 11 and 14 years old) participated in this study. Main outcome measures: Body mass index (BMI) percentiles specific for age and gender were obtained. Frequency of food and drinks purchased from fast food outlets and takeaway outlets over a weekly period and preferred types of drinks and food products usually consumed were measured. Results: More than 50% of the children in our survey purchased food or drinks from fast food or takeaway outlets twice or more a week, with about 10% consuming fast food or drinks from these outlets daily. About 70% of these children from Black ethnic groups and 54% of Asians purchased fast food more than twice a week. BMI has a significantly inverse relationship to fast food consumption. However, when age and gender are accounted, the BMI age–gender percentile is no longer significantly related to fast food consumption. Conclusions: This study revealed a very high frequency of fast food consumption among the schoolchildren. Taste, quick access and peer influence were major contributing factors. These schoolchildren are exposed to an obesogenic environment, and it is not surprising that in this situation, many of these children are already overweight and will likely become obese as adults.